Speech Act in Disney Animation The Boss Baby: Family Business by Michael McCullers - Manturino, Thesdya Ekareski; Moelier, Dahlia D.; Abeng, Andi Tenri (Humaniora: Journal of Linguistics, Literature, and Education, 2023)
This research objective was aimed to find out the kinds of speech acts and to describe the meaning of speech acts found in the movie script of The Boss Baby: Family Business written by Michael McCullers. To find the aimed objectives, this research then used qualitative descriptive method in analysing the data. The data were obtained by reading, identifying, classifying the words that includes speech acts in character's utterance in the movie script by applying Austin and Searle's theories. The results of the research then reveal that there are three kinds of speech acts were used in the movie script The Boss Baby: Family Business: they are locutionary, illocutionary, and perlocutionary. From the result it is found that each speech act has a different meaning from each category in each kinds of speech act, such as locution (imperative, interrogative, and declarative), illocution (assertive, directive, commissive, expressive, and declaration), then perlocution (act of convincing, act of scaring, act of insulting, and act of amusing). The locutionary act was the dominating speech act found in the movie script The Boss Baby: Family Business.